Some aspects of the animal ecology of Rhenosterbos: Elytropappus rhinocerotis (L.f.) Less - Shiff, Clive Julian (Rhodes University, Faculty of Science, Department of Zoology, 1957)
Rhenosterbos, Elytropappus rhinocerotis (L.f.) Less belongs to a purely South African section ot the Compositae. It is restricted to an area of low rainfall which is evenly distributed over the year. The plant is a specialised xerophyte with minute leaves and white pubescent twiglets. Older stems become woody and dry and bear no leaves. The shrubs have a life span of about eight years; the plants are most succulent and luxurious during the third and fourth year, after which they tend to become woody and scraggly. For this investigation insect material was obtained by sweep-net collection and field observation. In the Grahamatown district 78 collections were made during the period March - November 1953, with data thus obtained being embodied in this work. In addition to this, collections were made in the Cradock-Hofmeyer, Uitenhage, Riversdale, Bot River, Swellendam and Stellenbosch districts. Twenty species of insects have been shown definitely to feed on the plant and there are another 13 which probably feed on it. Of the 20 species attached to the plant, 12 are sucking forms belonging to the Orders Homoptera and Hemipters. They include six Coccids, two Jassids a Cercopid, two Mirids and a Pentstomid. The Coleoptera are represented by one or perhaps two species which feed on the plant. The Lepidoptera are represented by two important species of moth, a Geometrid and a Pyralid. Four species of gall forming Diptera are associated with the plant. There are two species of Trypetidae which are responsible for piriform swellings of growth points and are distributed evenly throughout the bush. There are also two Cecidomyidae one of which develops in the growth points of the shoots and is responsible tor a minute tubular gall. The other develops in a fusiform stem gall. This latter gall has been shown to be more common on smaller bushes than on larger ones, implying that the adult female may show certain selective powers during oviposition. The size of the insect population is held in check by spiders mantids and other general predators. There are several Coccinellids which prey on the scale insects. Rhenosterbos supports a small, well regulated community of insects. The balance between plant and animal is very dellcate because of the high degree of specialisation of the plant. On occasions this balance has been known to break down, and the insects present in abundance have swamped and killed large patches of the plant.
Keywords: Animal ecology -- South Africa; Rhenosterbos